Variabilidade de cariotípica em araceae: número cromossômico e heterocromatina - Nascimento, Sarah do (2017)
The genus Anthurium has a Neotropical distribution, with karyotype predominance of x = 15, although some species show disploidy or polyploid variations. The karyotypes of seven species and different populations of Anthurium were analyzed using fluorochrome CMA and DAPI staining. The karyotypes were composed of meta- and submetacentric chromosomes, with numbers varying from 2n = 30 to 2n = 60. Supernumerary euchromatic chromosomes were observed in A. affine, and supernumerary heterochromatic chromosomes were observed in A. gladiifolium and A. petrophilum. Polyploidy was recurrent in the Anthurium species analyzed, with records of 2n = 30 and 60 in different A. pentaphyllum populations. Fluorochrome staining revealed different CMA+ banding distributions between diploid and polyploid cytotypes of A. pentaphyllum, suggesting structural alteration events. Anthurium petrophilum, on the other hand, showed a more consistent banding profile, with 10 to 12 proximal CMA bands in the three populations analyzed. DAPI+ /CMA0 regions occurred exclusively in populations of A. gracile and A. pentaphyllum. The heterochromatic fraction in Anthurium was found to be quantitatively variable among species and populations, which may be related with adaptive aspects, different environmental conditions, or phylogenetic position.